Study and conception of a mini CNC machine - علي قويدر, ذكير; البشير, شهوبة; محمد مصباح, بن عيشة (University of El-Oued, 2022)
"This project is a study and implementation of a CNC machine. where , in the first ,we mentioned a generalities concerning the CNC machine .Next , the components of the CNC machine which contains an electrical and a mechanical part are described ,then, we represented the software used to control the CNC system based on Arduino Uno .Finally we implemented and an assembly of the CNC machine prototype""This project is a study and implementation of a CNC machine. where , in the first ,we mentioned a generalities concerning the CNC machine .Next , the components of the CNC machine which contains an electrical and a mechanical part are described ,then, we represented the software used to control the CNC system based on Arduino Uno .Finally we implemented and an assembly of the CNC machine prototype"
مذكرات ماستر تخصص الات
Keywords: CNC, Arduino Uno, G-code, GRBL; GRBL ، G-code , Arduino Uno ، CNC